The Impact of Incident Postoperative Delirium on Survival of Elderly Patients After Surgery for Hip Fracture Repair - Gottschalk, Allan (Anesth Analg, 2015)
BACKGROUND: The impact of delirium on survival of elderly patients remains undetermined with conflicting results from clinical studies and meta-analysis. In this study we assessed the relationship between long-term mortality and incident postoperative delirium in elderly patients undergoing hip fracture repair. METHODS: Patients ≥ 65 years old who were not delirious before undergoing hip fracture repair were included in a database maintained prospectively from March 1999 until July 2009. All participating patients underwent delirium assessment on the 2(nd) postoperative day using the confusion assessment method. Survival of the participants was determined as of October 2012. RESULTS: In 459 patients the mean (SD) period of evaluation from surgery until death or study closure was 4.1 (3.5) years with patients followed for as long as 13.6 years. Preoperative cognitive impairment was present in 120 patients (26.1%) and delirium on the 2(nd) postoperative day was observed in 151 (32.9%) of these. Although univariate analysis demonstrated a strong association between incident postoperative delirium and survival, this relationship did not persist in a multivariate model. Survival was a function of age at the time of surgery (p < 0.001), illness severity as determined by the ASA physical status score (p < 0.001), and duration of admission to the intensive care unit after surgery (p < 0.001). Incorporation of incident postoperative delirium did not meaningfully (p = 0.22) enhance the final survival model. In such a model, the hazard ratio [CI95] for incident postoperative delirium was 1.25 [0.92, 1.48]. CONCLUSIONS: Incident postoperative delirium was not significantly associated with decreased survival in elderly patients undergoing hip fracture repair.